Análisis del comportamiento del consumidor de compra de medicina alternativa natural en la ciudad de Machala - Ortiz Valarezo, Verónica Magdalena (2015)
The government is pushing for changes in the productive matrix, therefore being developed in the agricultural system new ways to expand the raw material and the various medicinal plants that serve to develop natural products making this source in the new alternative medicine that will improve the health of people, the evolution of consumer behavior generates competitiveness in various business fields, one of which is alternative medicine that has revolutionized the drug trade system; in actuality, consumers for products containing chemicals are switching to use alternative medicine for its great benefits of each of medicinal plants.